A role for lnc-DILC in liver cancer stem cells - Zhou, Tengfei; Wang, Fang (Translational Cancer Research, 2017)
As the sixth most common malignant tumor, the mortality rate of hepatocellular carcinoma (HCC) is the second highest worldwide (1). Despite the great amount of progress regarding the diagnosis and treatment for HCC in recent years, the long-term survival of HCC patients remains unsatisfactory. Dismal prognosis and frequent recurrence of HCC has limited patients’ survival (2). Therefore, new targets for HCC diagnosis and treatment and the strategy for research on HCC are required to be adjusted efficiently. Liver cancer stem cells (LCSCs) have the ability of selfrenewal and multi-directional differentiation, which are considered to be the origin of HCC initiation, propagation, metastasis, relapse and chemo-resistance (3). However, the regulatory mechanism of LCSCs is still unclear. It is constructive to study the molecular mechanism of LCSCs in the pathogenesis of HCC progression. At the same time, finding new therapeutic targets regarding LCSCs is also significant. Recent studies found that long noncoding RNAs (lncRNAs), present widely in eukaryotes, are involved in the regulation of diverse physiological and pathological processes in various cancers. Some evidence has indicated that lncRNAs participate in the regulation of the occurrence and development of HCC (4), and play a role in the maintenance and differentiation of the HCC cells (5). However, there are still lots of gaps between the function and mechanism of lncRNAs in LCSCs.